PENGARUH KOMUNIKASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT BENUA ASIA INDONETWORK MEDAN - Livia Pratama; Kristin Natalia Pasaribu; Pratiwi Eka Sari; Made Adhiguna Samvara; Ira Andira (JURNAL ILMIAH SIMANTEK, 2018)
The object of research is currently at PT. Benua Asia Indonetwork Medan object selection is causedby a decrease in employee performance. Employee performance is the contribution that employees give toorganizations or companies. Employee performance that is not good will directly reduce the company'sperformance and the stability of the company. The problem of employee performance needs to be addressedproperly, otherwise it will disrupt the stability of the company. Communication is a process in which someoneor some people use information to connect with the environment and other people Job stress is a feeling ofstress experienced by employees in the face of their work. Job stress is something that often occurs inemployees when performing tasks assigned by the leader. The theory used in this research is humanresource management theories relating to communication, work stress and performance. The researchmethod is a quantitative approach. The data testing technique uses a saturated sampling formula. Methodsof collecting data by conducting interviews, questionnaires and documentation studies. The analytical methodused is multiple linear regression, the coefficient of determination of the test simultaneously (Test-F) andpartially (Test-t). The population used is employees of 76 people and the number of samples used is 76people. The results showed that communication and work stress simultaneously and partially had asignificant effect on performance with a coefficient of determination 28% and the remaining 72% wasexplained by independent variables that were not examined such as leadership, discipline andcommunication. With the value of Fcount> Ftable (15,557> 3,12) and the value of t test t count>communication variable table (2,084> 1,993) and work stress variable (4,523> 1,993). Thus workcommunication and stress have a positive and significant effect on employee performance